(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article provides a scientific-theoretical and practical analysis of the current state of improving spelling literacy among prospective primary school teachers in mother tongue lessons. The study examines the role of spelling literacy in the professional training of primary school teachers, the factors influencing its formation, and the existing educational practices in higher education institutions. Based on pedagogical experience and scientific sources, the level of orthographic preparedness of future teachers is assessed, existing problems are identified, and scientifically grounded conclusions aimed at overcoming these challenges are formulated.